Microsoft Sway 365 to Develop Discovery Learning- Based E-module for Grade IV Elementary Students - Yola Monica Efriani; Alwen Bentri (STAI Hubbulwathan Duri, 2023)
The objective of this project was to develop e-modules using the current Microsoft Sway 365 platform, with a focus on discovery learning. The creation of the e-module dilator is driven by the discovery that current mathematics e-modules fail to effectively assist students in freely constructing knowledge and grasping topics. Students continue to see mathematics as challenging to comprehend, resulting in persistently low academic achievements in the subject. This research falls under the category of Research and Development (RD) and utilises the Plomp model. The Plomp model comprises three distinct stages: basic research, prototype phase, and assessment. The data gathering procedures employed consist of observation sheets, questionnaires, and test sheets. This study included descriptive and statistical methodologies. The investigation yields products that fall within a legitimate category value range of 4.2. This indicates that the e-module is appropriate for use by fourth-grade primary school students.